GPS positioning improvement by mitigating the ionospheric horizontal gradient - Sa’at, Nabila (2016)
A 3D ionospheric model was developed using TC3D and IRI to enhance the effect of the ionosphere to the GPS signals. Four comparisons have been done to see the effect of the DGPS positioning such as baselines length (short and long), low and high solar activity, range measurement from three and eight satellites and two different duration times (one and three hours). Some improvements can be seen after the corrections and it was a noticeable positioning improvement at the user location over the equatorial region. Improvement in the final positioning error can be found for all cases; with and without ionospheric corrections. From the results, positioning improvement has been achieved where only 26% of percentage error is from short baseline, 27% of percentage error from low solar activity, percentage error from 24% of 8 satellites and 40% of 3 hours period of time. It shows that it is important to consider criteria such as shorter baseline with more satellites viewing for longer duration of time (in hour) during low solar activity to achieve the improvement in the positioning. The effect of the ionospheric horizontal gradient which is more noticeable in the equatorial region has been resolved and will be very beneficial to improve the positioning of the user location, especially in applications such as surveying, geophysics, navigation and aviation.